Method for recovering scandium and zirconium from waste solid fuel cells
Patent Information
- Application Number
- CN202511427950.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2025-09-30
- Publication Date
- 2026-10-16
- Estimated Expiration
- 2045-09-30
AI Technical Summary
[0008]本发明的目的在于提供一种废旧固体燃料电池中回收钪和锆的方法,本发明采用碱熔活化-梯度酸浸-络合沉锆-协同萃钪的方法,将废旧固体燃料电池中的有价金属锆、钪进行单独回收,解决了废旧固体燃料电池中铁镍、硅酸盐等难过滤、杂质元素与钪和锆分离困难等问题,高效实现钪与锆的单独分离
[0048] (1) This invention employs an alkaline fusion activation-gradient acid leaching-zirconium complexation precipitation-scandium synergistic extraction method to separately recover valuable metals zirconium and scandium from spent solid fuel cells. This solves the problems of difficult filtration of iron-nickel and silicates, and difficulty in separating impurity elements from scandium and zirconium in spent solid fuel cells, achieving efficient separation of scandium and zirconium. The method has a low overall loss rate and high recovery rate, and the zirconium salt and scandium oxide products have high purity. It features a short process, low energy consumption, low cost, and minimal environmental pollution.
Smart Images

Figure CN121204402B_ABST
Abstract
Description
Technical Field
[0001] This invention belongs to the field of solid waste resource utilization technology, and relates to a method for recovering scandium and zirconium from waste solid fuel cells. Background Technology
[0002] Solid oxide fuel cells (SOFCs) are all-solid-state devices that directly convert the chemical energy of fuel into electrical energy through an electrochemical reaction, belonging to the third generation of fuel cells. Their low material cost (no precious metals required), high efficiency (nearly 60% self-generated electricity, and up to 85% energy efficiency through heat recovery and reuse), and fuel flexibility will make them an indispensable part of future energy systems.
[0003] In solid oxide fuel cells (SOFCs), scandium oxide primarily serves as a dopant in the electrolyte material, stabilizing the zirconia matrix and forming a high-performance electrolyte. This addresses the high-temperature operation bottleneck of SOFCs, achieving a balance between high ionic conductivity, structural stability, and mid-temperature operation. Establishing an efficient and sustainable waste recycling system for solid oxide fuel cells is a key breakthrough for promoting the iteration of clean energy technologies and the recycling of resources.
[0004] SOFC electrolyte waste contains 5-12% scandium oxide, 86-94% zirconium oxide, and small amounts of nickel, chromium, and rare earth elements. Among them, the recovery of scandium and zirconium is of high value, especially the rare earth element scandium metal, which is scarce and high-purity scandium oxide in SOFC is expensive.
[0005] CN111683903A discloses a method for recovering metal compounds from solid oxide fuel cell waste, comprising processing the solid oxide fuel cell waste to form a powder; digesting the processed waste; extracting lanthanum oxide and cerium oxide from a solution containing the digested processed waste; extracting a zirconium compound from the solution after extracting the lanthanum oxide and cerium oxide; and extracting a scandium compound from the solution from which the zirconium compound has been extracted.
[0006] CN103553128A discloses a method for recovering scandium oxide and zirconium oxide from scandium oxide-stabilized zirconia sintered bodies. The method includes the following steps: 1. Crushing the waste ceramic pieces of scandium oxide-stabilized zirconia using coarse crushing and fine grinding equipment until the average particle size is greater than 10 μm and less than or equal to 100 μm; 2. Mixing and melting the crushed waste ceramic pieces of scandium oxide-stabilized zirconia with a dissolving system at a ratio of 1:3 to 10; 3. Leaching and dissolving the mixture with dilute hydrochloric acid solution; 4. Removing Zr from the leaching solution using a complexation precipitation method. 4+ Ion precipitation recovery, followed by filtration, washing, and calcination to obtain the corresponding zirconium compounds; 5. Recovery of Sc 3+The ions were collected, and the filtrate and washings were enriched and purified by multiple precipitation methods with ammonia, oxalic acid or tartrate to obtain pure scandium oxide.
[0007] The aforementioned recycling methods are complex, energy-intensive, and have poor recovery efficiency for scandium and zirconium. Therefore, developing a short-process, low-energy closed-loop process for recovering valuable metals scandium and zirconium from SOFCs is particularly important. Summary of the Invention
[0008] The purpose of this invention is to provide a method for recovering scandium and zirconium from spent solid fuel cells. This invention employs an alkaline fusion activation-gradient acid leaching-zirconium complexation precipitation-scandium synergistic extraction method to separately recover the valuable metals zirconium and scandium from spent solid fuel cells. This method solves the problems of difficult filtration of iron-nickel and silicates, and difficulties in separating impurities from scandium and zirconium in spent solid fuel cells, achieving efficient separation of scandium and zirconium. The method is simple to operate, has a low overall loss rate, low energy consumption, and high recovery rate, and produces high-purity zirconium salt and scandium oxide products. It features a short process, low energy consumption, low cost, and minimal environmental pollution.
[0009] To achieve this objective, the present invention adopts the following technical solution:
[0010] This invention provides a method for recovering scandium and zirconium from spent solid fuel cells, the method comprising the following steps:
[0011] (1) The waste solid fuel cell was crushed and then subjected to magnetic separation to obtain waste powder;
[0012] (2) The waste powder is mixed with an alkali source, and after alkali fusion activation treatment, it is ultrasonically washed to obtain activated material;
[0013] (3) The activated material is subjected to gradient acid leaching to obtain an acid leaching solution;
[0014] (4) The acid leaching solution is mixed with a complexing agent to carry out a zirconium precipitation reaction, and the zirconium salt precipitate and zirconium precipitation mother liquor are obtained by solid-liquid separation treatment;
[0015] (5) Extract the mother liquor of zirconium precipitation to obtain a scandium-containing organic phase, back-extract the scandium-containing organic phase, and separate the solid and liquid to obtain scandium salt precipitate.
[0016] This invention involves crushing spent solid fuel cells and then magnetically separating them to remove magnetic materials such as nickel and iron, thus avoiding interference with subsequent chemical separation. Next, an alkaline fusion activation treatment is performed, where the alkali source reacts with scandium oxide and zirconium oxide in the waste at high temperature to generate soluble salts or easily acid-leached intermediate phases (both zirconium oxide and scandium oxide are sparingly soluble oxides, generally requiring strong acids or high temperatures to dissolve), significantly improving their acid reactivity. Then, a gradient acid leaching process is used to selectively leach scandium and zirconium, inhibiting the dissolution of impurities. Finally, zirconium is first precipitated via complexation, followed by scandium precipitation through extraction back-extraction, achieving atomic-level separation of Sc and Zr.
[0017] Preferably, the mesh size of the material obtained after crushing in step (1) is <200 mesh.
[0018] Preferably, the magnetic field strength of the magnetic separation in step (1) is 50mT~100mT, for example: 50mT, 60mT, 70mT, 80mT, 90mT or 100mT, etc., and is not limited to the listed values. Other unlisted values within this range are also applicable.
[0019] Preferably, the alkali source in step (2) includes sodium hydroxide.
[0020] Preferably, the mass ratio of the waste powder to the alkali source in step (2) is 1:(2~3), for example: 1:2, 1:2.2, 1:2.5, 1:2.8 or 1:3, etc., not limited to the listed values, other unlisted values within this range are also applicable.
[0021] Preferably, the alkaline fusion activation treatment in step (2) includes pre-melting and melt activation in sequence.
[0022] Preferably, the pre-melting temperature is 180℃~220℃, for example: 180℃, 190℃, 200℃, 210℃ or 220℃, etc., and is not limited to the listed values. Other unlisted values within this range are also applicable.
[0023] Preferably, the pre-melting time is 1h to 2h, for example: 1h, 1.2h, 1.5h, 1.8h or 2h, etc., and is not limited to the listed values. Other unlisted values within this range are also applicable.
[0024] Preferably, the melting activation temperature is 250℃~300℃, for example: 250℃, 260℃, 270℃, 280℃, 290℃ or 300℃, etc., and is not limited to the listed values. Other unlisted values within this range are also applicable.
[0025] Preferably, the melting activation time is 2h to 4h, for example: 2h, 2.5h, 3h, 3.5h or 4h, etc., and is not limited to the listed values. Other unlisted values within this range are also applicable.
[0026] Preferably, the ultrasonic frequency of the ultrasonic water washing in step (2) is 40kHz~100kHz, for example: 40kHz, 50kHz, 60kHz, 80kHz or 100kHz, etc., and is not limited to the listed values. Other unlisted values within this range are also applicable.
[0027] Preferably, the acid leaching solution used in the gradient acid leaching treatment in step (3) includes any one or a combination of at least two of hydrochloric acid, sulfuric acid, or nitric acid. Typical but non-limiting combinations include combinations of hydrochloric acid and sulfuric acid, combinations of hydrochloric acid and nitric acid, or combinations of sulfuric acid and nitric acid.
[0028] Preferably, the molar concentration of the acid leaching solution is 2 mol / L to 4 mol / L, for example: 2 mol / L, 2.5 mol / L, 3 mol / L, 3.5 mol / L or 4 mol / L, etc., and is not limited to the listed values. Other unlisted values within this range are also applicable.
[0029] Preferably, the gradient acid leaching treatment in step (3) includes performing a first acid leaching and a second acid leaching sequentially.
[0030] Preferably, the temperature of the first acid leaching is 55℃~65℃, for example: 55℃, 58℃, 60℃, 62℃ or 65℃, etc., and is not limited to the listed values. Other unlisted values within this range are also applicable.
[0031] Preferably, the first acid leaching time is 1h to 2h, for example: 1h, 1.2h, 1.5h, 1.8h or 2h, etc., and is not limited to the listed values. Other unlisted values within this range are also applicable.
[0032] Preferably, the temperature of the second acid leaching is 75°C to 85°C, for example: 75°C, 78°C, 80°C, 82°C or 85°C, etc., and is not limited to the listed values. Other unlisted values within this range are also applicable.
[0033] Preferably, the second acid leaching time is 2h to 4h, for example: 2h, 2.5h, 3h, 3.5h or 4h, etc., and is not limited to the listed values. Other unlisted values within this range are also applicable.
[0034] Preferably, the complexing agent in step (4) includes ammonium tartrate.
[0035] Preferably, the molar ratio of the complexing agent to the zirconium ions in the acid leaching solution in step (4) is (1.2~1.5):1, for example: 1.2:1, 1.25:1, 1.3:1, 1.4:1 or 1.5:1, etc., and is not limited to the listed values. Other unlisted values within this range are also applicable.
[0036] Preferably, the extraction system used in step (5) includes a synergistic extraction system of hexabutyltriphosphoric acid triamine (HBTMPP) and tri-n-octylphosphine oxide (TOPO).
[0037] Preferably, the molar concentration of HBTMPP in the synergistic extraction system is 0.5 mol / L to 1 mol / L, for example: 0.5 mol / L, 0.6 mol / L, 0.8 mol / L, 0.9 mol / L or 1 mol / L, etc., and is not limited to the listed values. Other unlisted values within this range are also applicable.
[0038] Preferably, the molar concentration of TOPO in the synergistic extraction system is 0.2 mol / L to 5 mol / L, for example: 0.2 mol / L, 0.25 mol / L, 0.3 mol / L, 0.4 mol / L or 0.5 mol / L, etc., and is not limited to the listed values. Other unlisted values within this range are also applicable.
[0039] Preferably, the stripping agent used in step (5) includes an oxalic acid solution.
[0040] Preferably, the mass concentration of the oxalic acid solution is 30 g / L to 60 g / L, for example: 30 g / L, 35 g / L, 40 g / L, 50 g / L or 60 g / L, etc., and is not limited to the listed values. Other unlisted values within this range are also applicable.
[0041] Preferably, stirring is performed during the back-extraction process described in step (5).
[0042] Preferably, the stirring time is 2h to 4h, for example: 2h, 2.5h, 3h, 3.5h or 4h, etc., and is not limited to the listed values. Other unlisted values within this range are also applicable.
[0043] Preferably, the back-extraction process described in step (5) is followed by a static phase separation process.
[0044] Preferably, the scandium salt precipitate in step (5) is calcined to obtain scandium oxide.
[0045] Preferably, the calcination temperature is 800℃~1000℃, for example: 800℃, 850℃, 900℃, 950℃ or 1000℃, etc., and is not limited to the listed values. Other unlisted values within this range are also applicable.
[0046] Preferably, the calcination time is 3h to 6h, for example: 3h, 3.5h, 4h, 5h or 6h, etc., and is not limited to the listed values. Other unlisted values within this range are also applicable.
[0047] Compared with the prior art, the present invention has the following beneficial effects:
[0048] (1) This invention employs an alkaline fusion activation-gradient acid leaching-zirconium complexation precipitation-scandium synergistic extraction method to separately recover valuable metals zirconium and scandium from spent solid fuel cells. This solves the problems of difficult filtration of iron-nickel and silicates, and difficulty in separating impurity elements from scandium and zirconium in spent solid fuel cells, achieving efficient separation of scandium and zirconium. The method has a low overall loss rate and high recovery rate, and the zirconium salt and scandium oxide products have high purity. It features a short process, low energy consumption, low cost, and minimal environmental pollution.
[0049] (2) In the method for recovering scandium and zirconium from waste solid fuel cells described in this invention, the leaching rate of zirconium can reach more than 99.1%, the leaching rate of scandium can reach more than 98.7%, the precipitation rate of zirconium during the complexation precipitation process can reach more than 99.3%, the loss rate of scandium can reach less than 0.7%, the purity of scandium oxide obtained can reach more than 99.9%, and the scandium recovery rate of the whole process can reach more than 97.1%. Attached Figure Description
[0050] Figure 1 This is a schematic diagram of the process flow for recovering scandium and zirconium from spent solid fuel cells according to an embodiment of the present invention. Detailed Implementation
[0051] The technical solution of the present invention will be further illustrated below through specific embodiments. Those skilled in the art should understand that the embodiments described are merely illustrative of the present invention and should not be construed as limiting the invention in any way.
[0052] The composition of the solid fuel cell waste used in the embodiments and comparative examples of this invention is as follows:
[0053] ZrO2: 90%, Sc2O3: 7%, NiO: 1.5%, Cr2O3: 1%, others (including rare earth oxides, SiO2, Al2O3, etc.): 0.5%.
[0054] Example 1
[0055] This embodiment provides a method for recovering scandium and zirconium from spent solid fuel cells, the method comprising the following steps:
[0056] (1) The solid fuel cell waste is crushed and ground to below 200 mesh, and iron and nickel impurities are removed by magnetic separation under a magnetic field strength of 50mT to obtain waste powder;
[0057] (2) Mix waste powder with sodium hydroxide at a mass ratio of 1:2, pre-melt at 200℃ for 1h to break the surface grain boundaries, then heat to 280℃ and melt at a constant temperature for 2h to obtain the melt. Wash the melt with 40kHz ultrasonic water to remove soluble silicates and obtain activated material.
[0058] (3) The activated material was subjected to a first acid leaching at 60°C for 1 hour using 2 mol / L hydrochloric acid, and then the temperature was raised to 80°C for a second acid leaching for 2 hours to obtain the acid leaching solution.
[0059] (4) Add ammonium tartrate complexing agent to the acid leaching solution according to the molar ratio of complexing agent to zirconium ions in acid leaching solution of 1:1.2 to generate zirconium tartrate precipitate and zirconium mother liquor;
[0060] (5) The mother liquor of zirconium precipitation was extracted using a synergistic extraction system consisting of 0.5 mol / L HBTMPP and 0.2 mol / L TOPO. After mixing for 1 h, the phases were separated to obtain a scandium-containing organic phase. The scandium-containing organic phase was then back-extracted with 30 g / L oxalic acid solution at room temperature. After stirring for 2 h, the phases were separated by standing and washed three times with pure water to obtain scandium oxalate precipitate. The scandium oxalate precipitate was calcined at 800 °C for 3 h to obtain scandium oxide product.
[0061] Example 2
[0062] This embodiment provides a method for recovering scandium and zirconium from spent solid fuel cells, the method comprising the following steps:
[0063] (1) The solid fuel cell waste is crushed and ground to below 200 mesh, and iron and nickel impurities are removed by magnetic separation under a magnetic field strength of 100mT to obtain waste powder;
[0064] (2) The waste powder and sodium hydroxide are mixed at a mass ratio of 1:3. The surface grain boundaries are first destroyed by pre-melting at 180℃ for 2 hours, and then the temperature is raised to 250℃ and kept constant for 4 hours to obtain the melt. The melt is washed with water using 80kHz ultrasonic waves to remove soluble silicates and obtain activated material.
[0065] (3) The activated material was subjected to a first acid leaching at 55°C for 2 hours using 4 mol / L hydrochloric acid, and then the temperature was raised to 75°C for a second acid leaching for 4 hours to obtain the acid leaching solution.
[0066] (4) Add ammonium tartrate complexing agent to the acid leaching solution according to the molar ratio of complexing agent to zirconium ions in acid leaching solution of 1:1.5 to generate zirconium tartrate precipitate and zirconium mother liquor;
[0067] (5) The mother liquor of zirconium precipitation was extracted using a synergistic extraction system consisting of 1 mol / L HBTMPP and 0.5 mol / L TOPO. After mixing for 2 hours, the phases were separated to obtain a scandium-containing organic phase. The scandium-containing organic phase was then back-extracted with 60 g / L oxalic acid solution at room temperature. After stirring for 2 hours and allowing the phases to separate, the phases were washed three times with pure water to obtain scandium oxalate precipitate. The scandium oxalate precipitate was calcined at 900℃ for 6 hours to obtain scandium oxide product.
[0068] Example 3
[0069] This embodiment provides a method for recovering scandium and zirconium from spent solid fuel cells, the method comprising the following steps:
[0070] (1) The solid fuel cell waste is crushed and ground to below 200 mesh, and iron and nickel impurities are removed by magnetic separation under a magnetic field strength of 80mT to obtain waste powder;
[0071] (2) The waste powder and sodium hydroxide are mixed at a mass ratio of 1:2. The mixture is first pre-melted at 220℃ for 1 hour to break the surface grain boundaries, and then heated to 300℃ for 2 hours to obtain the melt. The melt is then washed with water using 100kHz ultrasonic waves to remove soluble silicates and obtain the activated material.
[0072] (3) The activated material was subjected to a first acid leaching at 65°C for 1 hour using 3 mol / L hydrochloric acid, and then the temperature was raised to 85°C for a second acid leaching for 3 hours to obtain the acid leaching solution.
[0073] (4) Add ammonium tartrate complexing agent to the acid leaching solution according to the molar ratio of complexing agent to zirconium ions in acid leaching solution of 1:1.5 to generate zirconium tartrate precipitate and zirconium mother liquor;
[0074] (5) The mother liquor of zirconium precipitation was extracted using a synergistic extraction system consisting of 1 mol / L HBTMPP and 0.5 mol / L TOPO. After mixing for 2 hours, the phases were separated to obtain a scandium-containing organic phase. The scandium-containing organic phase was then back-extracted with 60 g / L oxalic acid solution at room temperature. After stirring for 2 hours and allowing the phases to separate, the phases were washed three times with pure water to obtain scandium oxalate precipitate. The scandium oxalate precipitate was calcined at 900℃ for 6 hours to obtain scandium oxide product.
[0075] Example 4
[0076] The only difference between this embodiment and Embodiment 1 is that the alkaline fusion activation treatment is performed directly at 280°C, while the other conditions and parameters are exactly the same as in Embodiment 1.
[0077] Example 5
[0078] The only difference between this embodiment and Embodiment 1 is that the melting activation temperature is 220°C, while the other conditions and parameters are exactly the same as in Embodiment 1.
[0079] Example 6
[0080] The only difference between this embodiment and Embodiment 1 is that the melting activation temperature is 350°C, while the other conditions and parameters are exactly the same as in Embodiment 1.
[0081] Example 7
[0082] The only difference between this embodiment and Embodiment 1 is that the temperature of the first acid leaching is 50°C, while the other conditions and parameters are exactly the same as in Embodiment 1.
[0083] Example 8
[0084] The only difference between this embodiment and Embodiment 1 is that the temperature of the first acid leaching is 70°C, while the other conditions and parameters are exactly the same as in Embodiment 1.
[0085] Example 9
[0086] The only difference between this embodiment and Embodiment 1 is that the temperature of the second acid leaching is 70°C, while the other conditions and parameters are exactly the same as in Embodiment 1.
[0087] Example 10
[0088] The only difference between this embodiment and Embodiment 1 is that the temperature of the second acid leaching is 90°C, while the other conditions and parameters are exactly the same as in Embodiment 1.
[0089] Comparative Example 1
[0090] The only difference between this comparative example and Example 1 is that ultrasonic water washing is not performed; all other conditions and parameters are exactly the same as in Example 1.
[0091] Comparative Example 2
[0092] The only difference between this comparative example and Example 1 is that step (2) does not involve alkaline fusion activation treatment; all other conditions and parameters are exactly the same as in Example 1.
[0093] Comparative Example 3
[0094] The only difference between this comparative example and Example 1 is that step (3) is only acid leaching at 80°C, while the other conditions and parameters are exactly the same as in Example 1.
[0095] Performance testing:
[0096] The leaching rates of zirconium and scandium in step (3) of the test examples and comparative examples, the zirconium precipitation rate and scandium loss rate in step (4), and the purity and recovery rate of scandium oxide obtained in step (4) are shown in Table 1.
[0097] Table 1
[0098]
[0099] As shown in Table 1, and based on Examples 1-10, the method for recovering scandium and zirconium from waste solid fuel cells described in this invention achieves a zirconium leaching rate of over 97% and a scandium leaching rate of over 96.5%. During the complexation and zirconium precipitation process, the zirconium precipitation rate reaches over 97.5%, the scandium loss rate is less than 2.5%, the obtained scandium oxide purity reaches over 99.7%, and the overall scandium recovery rate reaches over 92%. However, a high scandium loss rate does not necessarily lead to a low scandium recovery rate. Taking Examples 1 and 2 as examples, the scandium loss rate is the scandium loss during the complexation and zirconium precipitation process, not the overall process. Although Example 2 has a higher scandium loss rate compared to Example 1, the scandium leaching rate during the acid leaching process in Example 2 is higher than that in Example 1. Therefore, the overall scandium recovery rate is higher in Example 2 than in Example 1.
[0100] A comparison of Examples 1 and 4 shows that in the method for recovering scandium and zirconium from waste solid fuel cells described in this invention, alkaline fusion activation treatment affects the recovery of scandium and zirconium. The pre-melting treatment in this invention can destroy the surface grain boundaries of the waste powder and can significantly improve the activation effect of alkaline fusion activation.
[0101] A comparison of Examples 1 and 5-6 shows that in the method for recovering scandium and zirconium from waste solid fuel cells described in this invention, the melting activation temperature affects the activation effect. Controlling the melting activation temperature at 250℃~300℃ results in a better activation effect. If the melting activation temperature is too low, the activation reaction is insufficient, leading to a decrease in the leaching rate of zirconium and scandium. If the melting activation temperature is too high, it may cause some materials to be sintered or volatilized and lost, which also reduces the leaching rate of zirconium and scandium and increases the loss of scandium in the precipitation step.
[0102] A comparison of Examples 1 and 7-8 shows that in the method for recovering scandium and zirconium from waste solid fuel cells described in this invention, the temperature of the first acid leaching affects the acid leaching effect. Controlling the temperature of the first acid leaching at 55℃~65℃ results in a better acid leaching effect. If the temperature of the first acid leaching is too low, the acid leaching reaction rate is slow and scandium is not fully leached. If the temperature of the first acid leaching is too high, it may cause some zirconium to dissolve prematurely or increase the leaching of impurities.
[0103] A comparison of Examples 1 and 9-10 shows that in the method for recovering scandium and zirconium from waste solid fuel cells described in this invention, the temperature of the second acid leaching affects the leaching effect. Controlling the temperature of the second acid leaching at 75℃~85℃ results in a better leaching effect. If the temperature of the second acid leaching is too low, the zirconium will not be completely leached. If the temperature of the second acid leaching is too high, although the zirconium leaching rate is high, it may lead to an increase in the dissolution of impurities such as silicon (which is reflected in a slight decrease in the purity of scandium oxide in the subsequent process) and an increase in energy consumption.
[0104] As can be seen from the comparison between Example 1 and Comparative Example 1, in the method for recovering scandium and zirconium from waste solid fuel cells of the present invention, after alkaline fusion activation, the obtained melt needs to be ultrasonically washed to remove soluble silicates, thereby improving the acid leaching effect of zirconium and scandium.
[0105] As can be seen from the comparison between Example 1 and Comparative Example 2, in the method for recovering scandium and zirconium from waste solid fuel cells of the present invention, the alkaline fusion activation treatment allows the alkaline source to react with scandium oxide and zirconium oxide in the waste at high temperature to generate soluble salts or intermediate phases that are easily leached by acid, which can significantly improve their reactivity with acid.
[0106] As can be seen from the comparison between Example 1 and Comparative Example 3, in the method for recovering scandium and zirconium from waste solid fuel cells of the present invention, scandium and zirconium can be selectively leached by gradient acid leaching, impurity leaching is suppressed, and the purity and recovery rate of the obtained scandium and zirconium products are significantly improved.
[0107] The applicant declares that the above description is only a specific embodiment of the present invention, but the protection scope of the present invention is not limited thereto. Those skilled in the art should understand that any changes or substitutions that can be easily conceived by those skilled in the art within the technical scope disclosed in the present invention fall within the protection and disclosure scope of the present invention.
Claims
1. A method for recovering scandium and zirconium from spent solid fuel cells, characterized in that, The method includes the following steps: (1) The waste solid fuel cell was crushed and then subjected to magnetic separation to obtain waste powder; (2) The waste powder is mixed with an alkali source, and after alkali fusion activation treatment, it is ultrasonically washed to obtain activated material; (3) The activated material is subjected to gradient acid leaching to obtain an acid leaching solution; (4) The acid leaching solution is mixed with a complexing agent to carry out a zirconium precipitation reaction, and the zirconium salt precipitate and zirconium precipitation mother liquor are obtained by solid-liquid separation treatment; (5) Extraction treatment of the mother liquor of zirconium precipitation to obtain scandium-containing organic phase, back-extraction treatment of scandium-containing organic phase, solid-liquid separation to obtain scandium salt precipitate; The alkaline fusion activation treatment in step (2) includes pre-melting and melt activation in sequence. The temperature of the pre-melting is 180℃~220℃, and the temperature of the melt activation is 250℃~300℃.
2. The method as described in claim 1, characterized in that, The mesh size of the material obtained after crushing in step (1) is <200 mesh.
3. The method as described in claim 1, characterized in that, The magnetic field strength of the magnetic separation in step (1) is 50mT~100mT.
4. The method as described in claim 1, characterized in that, The alkali source in step (2) includes sodium hydroxide.
5. The method as described in claim 1, characterized in that, In step (2), the mass ratio of the waste powder to the alkali source is 1:(2~3).
6. The method as described in claim 1, characterized in that, The pre-melting time is 1 to 2 hours.
7. The method as described in claim 1, characterized in that, The melting activation time is 2h~4h.
8. The method according to any one of claims 1-4, characterized in that, The ultrasonic frequency of the ultrasonic water washing in step (2) is 40kHz~100kHz.
9. The method as described in claim 1, characterized in that, The acid leaching solution used in step (3) includes any one or a combination of at least two of hydrochloric acid, sulfuric acid, or nitric acid.
10. The method as described in claim 9, characterized in that, The molar concentration of the acid leaching solution is 2 mol / L to 4 mol / L.
11. The method as described in claim 1, characterized in that, Step (3) involves a gradient acid leaching process, which includes a first acid leaching and a second acid leaching in sequence.
12. The method as described in claim 11, characterized in that, The temperature of the first acid leaching is 55℃~65℃.
13. The method as described in claim 11, characterized in that, The first acid leaching time is 1 to 2 hours.
14. The method as described in claim 11, characterized in that, The temperature of the second acid leaching is 75℃~85℃.
15. The method as described in claim 11, characterized in that, The second acid leaching time is 2h~4h.
16. The method as described in claim 1, characterized in that, The complexing agent in step (4) includes ammonium tartrate.
17. The method as described in claim 1, characterized in that, The molar ratio of the complexing agent to the zirconium ions in the acid leaching solution in step (4) is (1.2~1.5):
1.
18. The method as described in claim 1, characterized in that, The extraction system used in step (5) includes a synergistic extraction system of hexabutyltriphosphoric acid triamine and tri-n-octylphosphine oxide.
19. The method as described in claim 18, characterized in that, The molar concentration of hexabutyltriphosphoric acid in the synergistic extraction system is 0.5 mol / L to 1 mol / L.
20. The method as described in claim 18, characterized in that, The molar concentration of tri-n-octylphosphine oxide in the synergistic extraction system is 0.2 mol / L to 5 mol / L.
21. The method as described in claim 1, characterized in that, The back-extraction agent used in step (5) includes oxalic acid solution.
22. The method as described in claim 21, characterized in that, The oxalic acid solution has a mass concentration of 30 g / L to 60 g / L.
23. The method as described in claim 1, characterized in that, Stirring is performed during the back-extraction process described in step (5).
24. The method as described in claim 23, characterized in that, The stirring time is 2 to 4 hours.
25. The method as described in claim 1, characterized in that, After the back-extraction process described in step (5), a static phase separation process is performed.
26. The method as described in claim 1, characterized in that, The scandium salt precipitate in step (5) is calcined to obtain scandium oxide.
27. The method as described in claim 26, characterized in that, The calcination temperature is 800℃~1000℃.
28. The method as described in claim 26, characterized in that, The calcination treatment time is 3h to 6h.
Citation Information
Patent Citations
Method for recovering scandia and zirconia from scandia stable zirconia sintered body
CN103553128A
Method of recovering metal compounds from solid oxide fuel cell scrap
CN111683903A
Method for producing high-purity discandium trioxide from alkali fusion separated anode slime / silver separating residue by use of total wet process
CN104726718A
Manufacturing method of matrix for fuel cell
JP1983166664A